2022
DOI: 10.1038/s41467-022-31709-2
|View full text |Cite
|
Sign up to set email alerts
|

CAF08 adjuvant enables single dose protection against respiratory syncytial virus infection in murine newborns

Abstract: Respiratory syncytial virus is a leading cause of morbidity and mortality in children, due in part to their distinct immune system, characterized by impaired induction of Th 1 immunity. Here we show application of cationic adjuvant formulation CAF08, a liposomal vaccine formulation tailored to induce Th 1 immunity in early life via synergistic engagement of Toll-like Receptor 7/8 and the C-type lectin receptor Mincle. We apply quantitative phosphoproteomics to human dendritic cells and reveal a role for Protei… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 93 publications
0
8
0
Order By: Relevance
“…Therefore, an ideal TB vaccination regimen would consist of a single administration for maximum coverage at minimal cost. Several studies support the notion that a single-dose vaccination regimen has the potential to be durably efficacious against other diseases [6][7][8][9][10][11] .…”
Section: Introductionmentioning
confidence: 92%
“…Therefore, an ideal TB vaccination regimen would consist of a single administration for maximum coverage at minimal cost. Several studies support the notion that a single-dose vaccination regimen has the potential to be durably efficacious against other diseases [6][7][8][9][10][11] .…”
Section: Introductionmentioning
confidence: 92%
“…It is evident that adaptive immune responses significantly change as age increases. Together with factors affecting innate immunity such as NK cell senescence and functionally distinct PRR responses as described previously [ 16 , 17 , 23 , 37 , 133 , 134 , 135 , 136 , 137 ], generating similar immune responses in adults and children seems challenging. Maturation of the innate and adaptive immune system in adults may partly explain the more favorable prognosis in children after an infection with COVID-19.…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%
“…The resulting impairment in early life to promote T-helper 1 immunity to novel pathogens can prime the immune system of children to the preferential induction of a tolerogenic or sometimes detrimental T-helper 2 response [ 29 , 32 , 33 ]. While these intrinsic features of the developing immune system may have proven disadvantageous in the context of other respiratory viruses such as RSV [ 34 , 35 , 36 , 37 , 38 ], it has been postulated that in the context of SARS-CoV-2 this may contribute to reduced disease burden in this age group [ 11 ]. In addition, investigation into the age-specific differences in pathology and immune response to infection could contribute to improved future vaccine formulations tailored for children.…”
Section: Introductionmentioning
confidence: 99%
“… 25 , 42–45 Preclinical research has suggested that this approach could be feasible in the immune system of newborns. 46 , 47 …”
Section: Introductionmentioning
confidence: 99%
“…25,[42][43][44][45] Preclinical research has suggested that this approach could be feasible in the immune system of newborns. 46,47 Notwithstanding the troubled history of hRSV vaccine development, intense research efforts in the past decades have led to several vaccine candidates in various stages of preclinical and clinical research, including subunit vaccines, 48,49 viral vector vaccines, [50][51][52] DNA-based vaccines, 53,54 and recombinant Mycobacterium bovis Bacillus Calmette-Guérin (BCG)-based vaccines, [55][56][57][58] among others. 48,49,[56][57][58][59][60][61][62][63][64] As with other areas of drug development, current efforts have tapped into the now extensive structural knowledge of hRSV to identify novel pharmacological targets.…”
Section: Introductionmentioning
confidence: 99%